Arabidopsis Protocols - Sanchez-Serrano, Jose J. (Methods in molecular biology, 2014)
Handling Arabidopsis Plants: Growth, Preservation of Seeds, Transformation and Genetic Crosses -- Using Arabidopsis Related Model Species (ARMS): Growth, Genetic Transformation and Comparative Genomics -- Growing Arabidopsis in vitro: Cell Suspensions, in vitro Culture, and Regeneration -- Arabidopsis Database and Stock Resources -- Bioinformatic Tools in Arabidopsis Research -- Exploiting Natural Variation in Arabidopsis -- Grafting in Arabidopsis -- Agrobacterium tumefaciens Mediated Transient Transformation of Arabidopsis thaliana Leaves -- iTilling: Personalized Mutation Screen -- Tailor Made Mutations in Arabidopsis Using Zinc-Finger Nucleases -- The Use of Artificial Micro RNA Technology to Control Gene Expression in Arabidopsis thaliana -- Generation and Identification of Arabidopsis EMS Mutants -- Generation and Identification of Arabidopsis T-DNA Insertion Mutants -- Identification of EMS-induced Causal Mutations in Arabidopsis thaliana by Next-Generation Sequencing -- Arabidopsis Transformation with Large Bacterial Artificial Chromosomes -- Global DNA Methylation Analysis Using Methyl-Sensitive Amplification Polymorphism (MSAP) -- Next Generation Mapping of Genetic Mutations Using Bulk Population Sequencing -- Chemical Fingerprinting of Arabidopsis Using Fourier-transform Infrared (FT-IR) Spectroscopic Approaches -- A Pipeline for 15N Metabolic Labeling and Phosphoproteome Analysis in Arabidopsis thaliana -- Gene Expression Profiling Using DNA Microarrays -- Forward Chemical Genetic Screening -- Highly-Reproducible ChIP-On-Chip Analysis to Identify Genome-Wide Protein Binding and Chromatin Status in Arabidopsis thaliana -- Fluorescence Microscopy -- Immunocytochemical Fluorescent In Situ Visualization of Proteins in Arabidopsis -- High Pressure Freezing and Freeze Substitution of Arabidopsis For Electron Microscopy -- Applications of Fluorescent Marker Proteins in Plant Cell Biology -- Flow Cytometry and Sorting in Arabidopsis -- Live Imaging of Arabidopsis Development -- Arabidopsis Organelle Isolation and Characterisation -- Analysis of Subcellular Metabolite Distributions within Arabidopsis thaliana Leaf Tissue: A Primer for Subcellular Metabolomics -- Hormone Profiling -- Purification of Protein Complexes and Characterization of Protein-Protein Interactions -- Protein Fragment Bimolecular Fluorescence Complementation Analysis for the In vivo Study of Protein-Protein Interactions and Cellular Protein Complex Localizations -- The Split Ubiquitin System for the Analysis of Three-Component Interactions -- RNA-Binding Protein Immunoprecipitation from Whole Cell Extracts -- High Throughput Analysis of Protein-DNA Binding Affinity.